2022
DOI: 10.1186/s13071-022-05441-1
|View full text |Cite
|
Sign up to set email alerts
|

A bloody interaction: plasma proteomics reveals gilthead sea bream (Sparus aurata) impairment caused by Sparicotyle chrysophrii

Abstract: Background Sparicotylosis is an enzootic parasitic disease that is well established across the Mediterranean Sea. It is caused by the polyopisthocotylean monogenean Sparicotyle chrysophrii and affects the gills of gilthead sea bream (GSB; Sparus aurata). Current disease management, mitigation and treatment strategies are limited against sparicotylosis. To successfully develop more efficient therapeutic strategies against this disease, understanding which molecular mechanisms and metabolic pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 91 publications
2
5
0
Order By: Relevance
“…Gene Ontology analyses from the purified EVs indicated biological processes related to blood (negative regulation of coagulation, iron ion transport, haemocyte migration and intracellular iron ion homeostasis; Fig. 4 A), consistent with the negative haemostatic impact [ 68 , 69 ] and catalytic process (regulation of catalytic activity and proteolysis) observed in infected S. aurata . Molecular functions revealed ferric and metal ion binding, ferroxidase activity, glutathione transferase and enzymatic activities related to oxidoreductase, transferase, hydrolase-peptidase, lyase, isomerase, ligase and translocase enzymes (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Gene Ontology analyses from the purified EVs indicated biological processes related to blood (negative regulation of coagulation, iron ion transport, haemocyte migration and intracellular iron ion homeostasis; Fig. 4 A), consistent with the negative haemostatic impact [ 68 , 69 ] and catalytic process (regulation of catalytic activity and proteolysis) observed in infected S. aurata . Molecular functions revealed ferric and metal ion binding, ferroxidase activity, glutathione transferase and enzymatic activities related to oxidoreductase, transferase, hydrolase-peptidase, lyase, isomerase, ligase and translocase enzymes (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…The liver fluke, F. hepatica , exhibits an extracellular digestion phase in its gut lumen [ 67 ], and a similar process is presumed in Eudiplozoon nipponicum (Goto, 1891) (Polyopisthocotyla: Diplozoidae) [ 10 ]. However, Riera-Ferrer et al [ 68 ] suggested that S. chrysophrii induces an intravascular haemolysis in its host, prior to ingesting the resulting blood meal. Thus, ESPs and EV-originating peptidases and peptidase inhibitors might have a crucial role in this parasite’s feeding strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The main clinical sign during sparicotylosis is anemia, which is caused by the hematophagous nature of a parasite ( 32 , 39 , 50 ). Furthermore, the parasite’s attaching mechanism to the gill filament through specialized clamps in its opisthaptor region ( 51 ) inflicts evident histopathological lesions such as lamellar synechiae and clubbing, resulting in disruption of the epithelium and marginal blood vessels ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The high stocking densities, the lack of fallowing strategies, and the enzootic locations of the off-shore cage farms are favoring parasite outbreaks and transmission. The growing concern in regard to the production losses has directed recent research efforts toward studies on the parasites’ biology ( 24 28 ), the host response ( 29 32 ), and the search for treatments ( 33 38 ). However, a closer look at the modulation of the mucous secretion and the goblet cells in the gills of gilthead seabream during the course of this parasitosis has not been thoroughly taken.…”
Section: Introductionmentioning
confidence: 99%
“…Sparicotylosis clinical progress, observed through the increase in infection levels reflects in the host serology. In total 22 proteins belonging to apolipoproteins, globins, and complement c3 were found significantly correlated with the infection intensity in plasma samples from fish undergoing low (1–50 monogeneans/fish), medium (51–100), and high (>100) infection 118 . The proteomics of host plasma showed perturbation of haemostasis, immunity, and lipid metabolism, and transport pathways, supporting the systemic response to the infection.…”
Section: Host Responsementioning
confidence: 91%